Pengaruh Green Marketing, Citra Merek, Dan Harga Terhadap Keputusan Pembelian Produk Tupperware (Studi Pada Mahasiswa Universitas Islam Malang) - Siti Masluhah; Muhammad Agus Salim; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to determine the effect of green marketing on purchasing decisions, to determine the effect of brand image on purchasing decisions, to determine the effect of price on purchasing decisions. The type of research used in this research is quantitative research. The sampling technique uses the Malhotra formula by multiplying the number of indicators by 5 to obtain 85 respondents. This study uses multiple linear regression analysis, by testing the hypothesis using the t test. The results of this study indicate that green marketing has a significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions, price does not have a significant effect on purchasing decisions. Keywords : Green Marketing, Brand Image, Price, Purchase Decision